2021
DOI: 10.7150/ijbs.56933
|View full text |Cite
|
Sign up to set email alerts
|

Enforced expression of miR-92b blunts E. coli lipopolysaccharide-mediated inflammatory injury by activating the PI3K/AKT/β-catenin pathway via targeting PTEN

Abstract: Endometritis is a reproductive disorder characterized by an inflammatory response in the endometrium, which causes significant economic losses to the dairy farming industry. MicroRNAs (miRNAs) are implicated in the inflammatory response and immune regulation following infection by pathogenic bacteria. Recent miRNA microarray analysis showed an altered expression of miR-92b in cows with endometritis. In the present study, we set out to investigate the regulatory mechanism of miR-92b in endometritis. Here, qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…In this study, we experimentally demonstrated that β-catenin in Wnt signaling negatively regulated the expression of inflammation and oxidative stress factors in LPS-treated BMECs, similar to the findings by Jiang et al [ 10 , 40 , 41 ]. In experiments of bovine endometrial epithelial cells stimulated with LPS, LPS was reported to inhibit the intracellular expression of β-catenin and promote inflammatory cell damage [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we experimentally demonstrated that β-catenin in Wnt signaling negatively regulated the expression of inflammation and oxidative stress factors in LPS-treated BMECs, similar to the findings by Jiang et al [ 10 , 40 , 41 ]. In experiments of bovine endometrial epithelial cells stimulated with LPS, LPS was reported to inhibit the intracellular expression of β-catenin and promote inflammatory cell damage [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we experimentally demonstrated that β-catenin in Wnt signaling negatively regulated the expression of inflammation and oxidative stress factors in LPS-treated BMECs, similar to the findings by Jiang et al [ 10 , 40 , 41 ]. In experiments of bovine endometrial epithelial cells stimulated with LPS, LPS was reported to inhibit the intracellular expression of β-catenin and promote inflammatory cell damage [ 40 ]. Moreover, β-catenin was found to negatively regulate the inflammatory response induced by Salmonella typhimurium , and stimulation of mouse models and colonic epithelial cells by this strain aided the degradation of β-catenin and increased the expression of IL-6 and TNF-α [ 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…Expression of miR-92b was significantly upregulated in the porcine placenta on day 90 of gestation ( Su et al, 2010 ). In a study reported in cattle, miR-92b (downregulated expression) was associated with endometritis, an inflammatory response in the endometrium that causes reproductive disorder ( Jiang et al, 2021 ). The authors further reported that over-expression of miR-92b significantly suppressed the activation of the toll-like receptor in lipopolysaccharide-mediated bovine endometrial cells, thereby reducing pro-inflammatory cytokines and inhibiting cell apoptosis ( Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endometrium, the first tissue layer exposed to bacteria, plays a vital role in protecting the uterus (Umar et al, 2021). An intact and healthy endometrium protects the uterus from bacteria (Jiang et al, 2021). However, recent studies have demonstrated that LPS damages the intact endometrium by inducing apoptosis in endometrial epithelial cells (Chen et al, 2021; Gao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%